[ATR] feature involves a distinct tongue root articulation: evidence from ultrasound imaging. - Hudu, F. (Elsevier - Lingua, 2014)
The feature [ATR] (Advanced Tongue Root) assumes a unique role of the tongue root in the production of [ ATR] vowels. However, whether the actual position of the tongue root accurately characterises vowel pairs distinguished by this feature has attracted some controversy. This paper tests the hypothesis that the [ATR] specification of a vowel maps onto a definite articulatory position of the tongue root. It further investigates whether such a mapping reflects which of the values of [ATR] is dominant in a language. The results of five ultrasound imaging experiments using Dagbani, a Gur language of Ghana, show that [þATR] vowels of all height specifications are produced with a more anterior tongue root than [ ATR] vowels. They also show that tongue body height, a plausible alternative to tongue root position, does not consistently define the distinction. More importantly, the results show that vowels specified for [þATR], the dominant value in Dagbani, are produced with a tongue root anterior displacement from a neutral position while the recessive [ ATR] vowels have variable tongue root positions. The results support a direct mapping between the phonological feature [ATR] and the articulatory gestures producing it.
Article
Keywords: Vowel harmony; [ATR]; Phonetics--phonology interface; Ultrasound imaging; Dagbani; Ghana